Pitting corrosion evaluation in aluminum alloy AA1050 - Garita-Arce, Luis (2014)
The aluminum poses a versatility of uses in modern life. The possibility of deterioration of pitting them is one of the main considerations for the manufacturer, in order to avoid claims. In this sense ASTM G100-89 proposes a method of assessment of aluminum by means of the evaluation of potential versus applying cyclic galvanic polarizations afford it protection potentials (Eprot) below which it can be exposed without waiting aluminum pitting. In this work pose assessment technique, evaluating pitting in AA1050 type aluminum, used for most of the usual applications. The variables considered were the usual exposure to aluminum in normal environments: composition, pH, temperature and strain rates. The tests performed according to ASTM G100-89 for alloys showed no significant differences considered, although it was observed that the AA1050 alloy has a greater susceptibility to pitting in areas of pH = 7 and with high deformations.